(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
In this study, the allele frequencies and some statistical parameters of forensic interest were determined for the fifteen short tandem repeat loci included in AmpFlSTR Identifiler (Applied Biosystems) genotyping kit in Nainital, Uttarakhand population. A total of 114 samples were analysed for the said study. All the analyzed loci met Hardy-Weinberg equilibrium expectations. They possess a high combined power of discrimination & high combined power of exclusion, showing them to be a group of excellent markers as complement in paternity testing, in the identification of individuals and in forensic applications in general.